Adjuvant therapy in renal cell carcinoma. (November 2017) - Massari, Francesco; Di Nunno, Vincenzo; Ciccarese, Chiara; Graham, Jeffrey; Porta, Camillo; Comito, Francesca; Cubelli, Marta; Iacovelli, Roberto; Heng, Daniel Y.C.
Highlights: Before TKi no adjuvant treatment has shown clinical efficacy in RCC. In ASSURE trial sunitinib failed to show a DFS benefit in patients with resected RCC. In S-TRAC study sunitinib has shown to increase DFS of patients with resected RCC. Sorafenib and pazopanib failed toshow a significant improvement in DFS in adjuvant setting. Adjuvant immunotherapy is a promising strategy currently under investigation. Abstract: Several drugs have demonstrated clinical activity in metastatic renal cell carcinoma (mRCC). The identification of key metabolic pathways has led to the development of novel targeted therapies which have drastically changed the treatment paradigm of mRCC. Moreover, immune-checkpoint inhibitors have recently shown significant activity in advanced disease. Despite these advancements, the role of adjuvant therapy in localized, non-metastatic RCC remains unclear. The utility of many of these agents in the adjuvant setting is currently being actively explored. In this review, we will summarize the main clinical trials investigating adjuvant therapy in renal cell carcinoma, focusing primarily on immunotherapy and targeted agents.